Building the niche through time: using 13, 000 years of data to predict the effects of climate change on three tree species in Europe. Issue 3 (15th May 2012) - Maiorano, L.; Cheddadi, R.; Zimmermann, N. E.; Pellissier, L.; Petitpierre, B.; Pottier, J.; Laborde, H.; Hurdu, B. I.; Pearman, P. B.; Psomas, A.; Singarayer, J. S.; Broennimann, O.; et al.
ABSTRACT Aim Species distribution models (SDMs) based on current species ranges underestimate the potential distribution when projected in time and/or space. A multi‐temporal model calibration approach has been suggested as an alternative, and we evaluate this using 13, 000 years of data. Location Europe. Methods We used fossil‐based records of presence for Picea abies, Abies alba and Fagus sylvatica and six climatic variables for the period 13, 000 to 1000 yr bp. To measure the contribution of each 1000‐year time step to the total niche of each species (the niche measured by pooling all the data), we employed a principal components analysis (PCA) calibrated with data over the entire range of possible climates. Then we projected both the total niche and the partial niches from single time frames into the PCA space, and tested if the partial niches were more similar to the total niche than random. Using an ensemble forecasting approach, we calibrated SDMs for each time frame and for the pooled database. We projected each model to current climate and evaluated the results against current pollen data. We also projected all models into the future. Results Niche similarity between the partial and the total‐SDMs was almost always statistically significant and increased through time. SDMs calibrated from single time frames gave different results when projected to current climate, providing evidence of a change in the species realized niches through time. Moreover, they predicted limited climate suitability when compared with the total‐SDMs. The same results were obtained when projected to future climates. Main conclusions The realized climatic niche of species differed for current and future climates when SDMs were calibrated considering different past climates. Building the niche as an ensemble through time represents a way forward to a better understanding of a species' range and its ecology in a changing climate.